2017
DOI: 10.7554/elife.22207
|View full text |Cite
|
Sign up to set email alerts
|

p27Kip1 promotes invadopodia turnover and invasion through the regulation of the PAK1/Cortactin pathway

Abstract: p27Kip1 (p27) is a cyclin-CDK inhibitor and negative regulator of cell proliferation. p27 also controls other cellular processes including migration and cytoplasmic p27 can act as an oncogene. Furthermore, cytoplasmic p27 promotes invasion and metastasis, in part by promoting epithelial to mesenchymal transition. Herein, we find that p27 promotes cell invasion by binding to and regulating the activity of Cortactin, a critical regulator of invadopodia formation. p27 localizes to invadopodia and limits their num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 100 publications
2
44
0
Order By: Relevance
“…A previous in vitro study has reported that PAK1 can act upstream of p27 to increase p27–cortactin interaction and PAK1‐mediated cortactin phosphorylation to promote the invasion of mouse embryonic fibroblasts (MEF) (Jeannot et al , ). However, this particular mechanism is not supported by our cytoplasmic p27 IP–MS data, where cortactin was not co‐immunoprecipitated with cytoplasmic p27 in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous in vitro study has reported that PAK1 can act upstream of p27 to increase p27–cortactin interaction and PAK1‐mediated cortactin phosphorylation to promote the invasion of mouse embryonic fibroblasts (MEF) (Jeannot et al , ). However, this particular mechanism is not supported by our cytoplasmic p27 IP–MS data, where cortactin was not co‐immunoprecipitated with cytoplasmic p27 in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, p27 kip1 was shown to physically interact with cortactin and mediate its interaction with the p21-activated kinase, PAK1. PAK1 phosphorylates cortactin on S113 and thereby promotes invadopodia turnover 21 . In that work, the authors suggest that the role of p27 kip1 in invadopodia function is restricted to the cytoplasmic compartment, without any links to its cell cyclerelated function in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Their mislocalization to the cytoplasm is associated with higher aggressiveness of several types of cancers, including breast cancer (Liang et al 2002;Roninson 2002;Shin et al 2002;Viglietto et al 2002;Winters et al 2001;Zhou et al 2001). Most recently, a study demonstrated that p27 kip1 facilitates invadopodia dynamics through the PAK1-cortactin axis (Jeannot et al 2017). Thus, further investigation is required to determine the molecular mechanism by which invadopodia-driven motility is coordinated with cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study has shown that the cytoplasmic pool of cyclin-dependent kinase inhibitor p27 is involved in regulation of ECM degradation. 44 On a similar note, anchor cell invasion into vulval epithelium, occurring during development in C. elegans, is only performed by cells that are in G0/G1 phase of the cell cycle. 45 Tumor cell arrest during the G1/S transition, by inhibitors of Cdk4/6, is one of the new avenues for breast carcinoma treatment.…”
Section: Discussionmentioning
confidence: 99%